Juridical Analysis Of Final Review Review (Pk) Of Criminal Corruption Cases By The Head Of Personnel Body Formation In Pagar Alam City - Rhamadani, Dwi Putri; Panggabean, Tardip; Jaya, Eni (Greenation International Journal of Law and Social Sciences, 2024)
This research is to find out the Legal Considerations of the Panel of Judges in imposing a criminal verdict on corruption committed by the Head of Formation of the Civil Service Agency in using his position in Pagar Alam City (Case study of Cassation Decision No. 2697 K/Pid.sus/2016, with PK No. 163/Pid.sus/2019). Where the regulations regarding the eradication of corruption are listed in Law No.20 of 2001 which has been revised in several articles. The formulation of the problem in this study How is the verdict of the panel of Judges at the Cassation level in the Supreme Court of the Republic of Indonesia with Number 2697 K / PID.SUS / 2016, against the perpetrators of abuse of authority due to acts of Corruption related to the appointment of honorer to CPNS, and how is the verdict of the Supreme Court Judges at the level of Reconsideration against the perpetrators of the crime of participation (article 55 of the Criminal Code) as the head official of the personnel formation field of Pagar Alam City with decision number: 163 PK/Pid.sus/2019. This research is a qualitative normative juridical research which is then presented descriptively by describing the problem and drawing conclusions to determine the results. The result of the research obtained is that the judge's consideration at the cassation level is not in accordance with the applicable law because the perpetrator is an official in a government office who abuses his authority so that it is appropriate for the decision of the supreme court judge at the cassation level to impose a sentence in accordance with the applicable law.